Copper-titanium etching solution with high stability and long service life as well as preparation method and application of copper-titanium etching solution
By optimizing the formulation of copper-titanium etching solution, using persulfates, organic acids, sulfonated cyclodextrins, bisulfate-containing acidic ionic liquids, fluorine compounds and polyols, the existing copper-titanium etching solution has solved the problems of short stability and life of existing copper-titanium etching solution, achieving high stability and long-life etching effect, and is suitable for precision electronic device processing.
Patent Information
- Application Number
- CN202510919100.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2045-07-04
AI Technical Summary
The existing copper-titanium etching liquid in the persulfate system has problems such as poor stability and short life during the etching process, resulting in fluctuations in etching rate and poor product yield.
The formulations of persulfate, organic acid, sulfonated cyclodextrin, acidic ionic liquid containing bisulfate, fluorine compounds and polyols are adopted to form a copper-titanium etching solution with high stability and long life by regulating the proportion of each component. The sulfonated cyclodextrin adjusts the etching rate, the acidic ionic liquid containing bisulfate maintains the stability of the etching solution, the fluorine compounds promote the oxidative dissolution of titanium, the organic acid stabilizes the complex, and the polyol prevents the precipitation of by-products.
It realizes high stability and long life of copper-titanium etching liquid, reduces local overetching and titanium residues, ensures etching uniformity and precise control of etching rate, and is suitable for precision etching of Cu/Ti stacks, reducing production costs.
Smart Images

Figure CN120400842A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of etching solutions, and particularly relates to a highly stable and long-life copper-titanium etching solution, a preparation method thereof, and an application thereof. Background Art
[0002] In the manufacturing of integrated circuits, PCBs, and display panels, the persulfate-based copper-titanium etching solution, based on the strong oxidizing property of persulfate, realizes selective etching by oxidizing copper and titanium into soluble metal ions. However, during the etching process, persulfate ions are continuously consumed, and a large amount of copper and titanium ions generated by the reaction accumulate; copper ions have a catalytic effect on the decomposition of persulfate, accelerating the ineffective consumption of persulfate ions, resulting in a rapid decline in the oxidation ability of the etching solution, and further leading to problems such as fluctuations in etching rate, local over-etching, or incomplete etching, seriously affecting the product yield and consistency. At the same time, when the etching solution is recycled, the pH value fluctuates, which further reduces the oxidation activity and stability of persulfate.
[0003] Patent KR1020200068131A discloses an etchant composition and a method for manufacturing a metal pattern and an array substrate using the etchant composition. The etchant composition contains persulfate, a tetrazine compound, a dichloro compound, a fluorine compound, and water. The weight ratio of the tetrazine compound to the dichloro compound is about 1:0.5 to about 1:4. The etchant composition can etch multi-layers of titanium / copper and can be used to manufacture metal patterns and array substrates with excellent etching pattern properties; however, this formulation does not effectively solve the stability problem caused by the attenuation of the oxidation ability of the etching solution.
[0004] Patent CN120006294A discloses a copper-titanium etching solution and a preparation method thereof. The copper-titanium etching solution includes potassium monopersulfate compound salt, sodium percarbonate, benzotriazole-2,3-dicarboxylic acid, 5-aminotetrazole, ethylenediaminetetraacetic acid tetrasodium, hydroxyethylidene diphosphonic acid, coconut oil amide propyl betaine, benzotriazole, 2-mercaptobenzothiazole, poly-N-isopropylacrylamide, potassium perchlorate, and the balance of ultrapure water. It mainly realizes the precise control of the copper-titanium etching rate and effectively inhibits undercutting and titanium residue; however, the service life of this etching solution is low, the storage period is also short, and the maximum copper ion loading is limited to 8300 ppm, which is difficult to meet the requirements of long-term and large-scale production.
[0005] Patent CN118957588A discloses a metal film wiring etching solution, a preparation method thereof, and an application thereof. The etching solution includes an oxidizing cerium salt, an organic sulfonic acid, a peroxide compound, a stabilizer, a functionalized ionic liquid, an amino acid-based oligomer, a pyrosulfate, an alcohol ether solvent, a Gemini surfactant, and the balance is water. This etching solution is only for the etching of wiring with different specifications and chromium composite film processes, and the etching effect depends on the oxidizing cerium salt; there is no precipitation after 72 h for the etching solution, but the etching performance is unknown.
[0006] Based on the above statements, the existing copper-titanium etching solution technology using persulfate system still has the defects of poor etching stability and short lifespan, and urgently needs to be improved. Summary of the Invention
[0007] To solve the above technical problems, one of the objectives of the present invention is to provide a copper-titanium etching solution with high stability and long lifespan.
[0008] The technical solution adopted by the present invention is as follows: A copper-titanium etching solution with high stability and long lifespan, calculated by mass percentage, includes: persulfate 5-15%, organic acid 3-15%, sulfonated cyclodextrin 0.5-3%, acidic ionic liquid containing bisulfate 0.1-4%, fluorine compound 0.05-1%, polyol 0.01-2%, and the balance is water.
[0009] Preferably, the persulfate is selected from at least one of potassium persulfate, sodium persulfate, and ammonium persulfate. The dosage of the persulfate is not limited to 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 12%, 13%, 14%, 15%.
[0010] Preferably, the sulfonated cyclodextrin is sulfobutyl-β-cyclodextrin. The dosage of the sulfonated cyclodextrin is not limited to 0.5%, 0.7%, 0.9%, 1.0%, 1.5%, 1.9%, 2.0%, 2.4%, 2.7%, 3.0%.
[0011] Preferably, the acidic ionic liquid containing bisulfate is selected from at least one of imidazole bisulfate ionic liquid, pyridine bisulfate ionic liquid, and pyrrolidone bisulfate ionic liquid. The dosage of the acidic ionic liquid containing bisulfate is not limited to 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%.
[0012] Preferably, the imidazole bisulfate ionic liquid is selected from at least one of 1-butyl-3-methylimidazole bisulfate, 1-carboxymethyl-3-methylimidazole bisulfate, and 1-hydroxyethyl-3-methylimidazole bisulfate; The pyridine bisulfate ionic liquid is selected from at least one of N-ethylpyridine bisulfate, N-butylpyridine bisulfate, and N-hexylpyridine bisulfate; The pyrrolidone bisulfate ionic liquid is selected from at least one of 2-pyrrolidone bisulfate, 1-methyl-2-pyrrolidone bisulfate, and 1-(3-sulfonic acid group)-propyl-2-pyrrolidone bisulfate.
[0013] Preferably, the fluorine compound is selected from at least one of hydrofluoric acid, ammonium fluoride, potassium fluoride, sodium fluoride, ammonium bifluoride, potassium bifluoride, and sodium bifluoride. The dosage of the fluorine compound is not limited to 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.7%, 0.9%, 1.0%.
[0014] Preferably, the organic acid is selected from at least one of citric acid, malic acid, acetic acid, propionic acid, oxalic acid, lactic acid, tartaric acid, and succinic acid. The dosage of the organic acid is not limited to 3%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 12%, 13%, 14%, 15%.
[0015] Preferably, the polyol is selected from at least one of diethylene glycol, ethylene glycol, glycerol, 1,2 - propanediol, 1,4 - butanediol, pentaerythritol, mannitol, and xylitol. The dosage of the polyol is not limited to 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.7%, 1.0%, 1.3%, 1.6%, 1.9%, 2.0%.
[0016] In the above formula, the persulfate acts as a strong oxidant in the etching solution, providing the oxidation ability required for etching. Through the oxidation reaction, copper and titanium metals are converted into soluble ions to achieve selective etching.
[0017] The acidic ionic liquid containing bisulfate not only provides hydrogen ions and bisulfate ions to maintain an acidic environment and promote the dissolution of metal ions, but also imidazole - type, pyridine - type, and pyrrolidone - type cations can adsorb on the surface of the metal film layer to inhibit the over - etching side reaction; at the same time, the cations can also form stable ion pairs with persulfate through electrostatic interaction and conjugation, slowing down the decomposition rate of persulfate and prolonging the life of the etching solution; compared with traditional inorganic bisulfates, the etching is more uniform.
[0018] Sulfonated cyclodextrin, on the one hand, the sulfonate ions have the function of accelerating the etching rate and adjusting the pH value of the etching solution, promoting uniform etching and reducing local over - etching or incomplete etching; on the other hand, through the cavity structure of cyclodextrin to encapsulate copper ions and complex copper ions with sulfonate ions, it can reduce the catalytic effect of copper ions on the decomposition of persulfate and prolong the life of the etching solution. And sulfonated cyclodextrin cooperates with the acidic ionic liquid containing bisulfate to effectively inhibit the ineffective decomposition of persulfate ions, delay the attenuation of oxidation ability, and thus obtain a highly stable and long - life copper - titanium etching solution.
[0019] Titanium is prone to form a dense titanium oxide passivation layer during the etching process, which hinders further reaction. Fluoride ions provided by fluorine compounds form soluble complexes with titanium ions, destroying the passivation layer and significantly increasing the etching rate of titanium; fluoride ions and persulfate act synergistically to accelerate the oxidative dissolution of titanium, avoid titanium residue, better regulate the etching rate ratio of copper / titanium, and reduce undercut or over-etching phenomena.
[0020] The carboxylate groups of organic acids form stable complexes with copper ions and titanium ions, reducing the adverse effects of metal ion accumulation on the system, while enhancing the solubility of etching products and reducing precipitation.
[0021] Polyols can prevent the precipitation of etching by-products, maintain the uniformity of the etching solution; reduce the risk of equipment pipeline blockage and improve process stability.
[0022] The second object of the present invention is to provide a preparation method of a highly stable and long-life copper-titanium etching solution as described above. According to the required ratio of the copper-titanium etching solution, persulfate, organic acid, sulfonated cyclodextrin, acidic ionic liquid containing bisulfate, fluorine compound, polyol and water are mixed to obtain it.
[0023] The third object of the present invention is to provide an application of a highly stable and long-life copper-titanium etching solution as described above in etching copper-titanium laminated materials.
[0024] The beneficial effects of the present invention are as follows: A new etching solution formulation is provided, using persulfate, organic acid, sulfonated cyclodextrin, acidic ionic liquid containing bisulfate, fluorine compound, polyol and water as raw materials. By regulating the dosage ratio, a highly stable and long-life copper-titanium etching solution is obtained. Sulfonated cyclodextrin can well regulate the etching rates of copper and titanium to ensure uniform etching; the acidic ionic liquid containing bisulfate can ensure that the etching solution maintains excellent etching performance for a long time and can effectively prevent the occurrence of local over-etching phenomena. The functionalized cation selectively adsorbs on the copper-titanium surface, reducing the long tailing phenomenon caused by incomplete titanium etching; sulfonated cyclodextrin and the acidic ionic liquid containing bisulfate act together. On the one hand, they can effectively inhibit the ineffective decomposition of persulfate ions and significantly enhance the stability of the etching solution. On the other hand, they can cooperate with the main oxidant persulfate to regulate the uniformity of the etching rate, inhibit lateral corrosion and reduce the tailing phenomenon.
[0025] Tests show that after dissolving 8000 ppm of copper powder and standing for 12 h, the present copper-titanium etching solution still has excellent etching performance and high stability of the etching solution; and even when the copper addition concentration is as high as 12000 ppm, the present copper-titanium etching solution can still accurately control the etching cone angle and the size of CD bias of the Cu / Ti laminate, reducing the size of the tailing.
[0026] The components in the copper-titanium etching solution act together to etch the solution evenly, reduce local over-etching or residues, and are suitable for the precision etching of Cu / Ti laminates. It has the advantages of high stability, long life, environmental friendliness, and strong process adaptability, and is suitable for the processing of precision electronic devices, effectively reducing production costs. Description of the Drawings
[0027] Figure 1 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Example 1 of the present invention. In the figure: 1 is the cone angle, 2 is the CD bais, and 3 is the tail; Figure 2 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Example 2 of the present invention. In the figure: 1 is the CDbais, 2 is the tail, and 3 is the cone angle; Figure 3 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Example 3 of the present invention. In the figure: 1 is the CDbais, 2 is the tail, and 3 is the cone angle; Figure 4 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Comparative Example 1 of the present invention. In the figure: 1 is the tail, 2 is the CD bais, and 3 is the cone angle; Figure 5 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Comparative Example 2 of the present invention. In the figure: 1 is the CDbais, 2 is the tail, and 3 is the cone angle; Figure 6 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Comparative Example 3 of the present invention. In the figure: 1 is the cone angle, 2 is the CD bais, and 3 is the tail; Figure 7 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Comparative Example 4 of the present invention. In the figure: 1 is the tail, 2 is the CD bais, and 3 is the cone angle; Figure 8 This is the SEM image of the etching effect of the high-stability and long-life copper-titanium etching solution in Comparative Example 5 of the present invention. In the figure: 1 is the cone angle, 2 is the CD bais, and 3 is the tail. Detailed Embodiments
[0028] For ease of understanding, the technical solutions of the present invention will be described in more detail below in conjunction with the embodiments. Unless otherwise specified, the terms used herein have the meanings commonly understood by those skilled in the art.
[0029] Example 1 A highly stable and long - life copper - titanium etching solution, by mass percentage, includes the following components: persulfate 10%, organic acid 8%, sulfonated cyclodextrin 1.5%, acidic ionic liquid containing bisulfate 2%, fluorine compound 0.5%, polyol 1.25%, and the balance is water.
[0030] Among them, the persulfate is ammonium persulfate; the organic acid is citric acid; the sulfonated cyclodextrin is sulfobutyl - β - cyclodextrin; the acidic ionic liquid containing bisulfate is 1 - butyl - 3 - methylimidazolium bisulfate; the fluorine compound is hydrofluoric acid; the polyol is diethylene glycol.
[0031] The preparation method is: mix the persulfate, organic acid, sulfonated cyclodextrin, acidic ionic liquid containing bisulfate, fluorine compound, polyol and water evenly according to the above formula to obtain it.
[0032] Example 2 A highly stable and long - life copper - titanium etching solution, by mass percentage, includes the following components: persulfate 5%, organic acid 15%, sulfonated cyclodextrin 3%, acidic ionic liquid containing bisulfate 4%, fluorine compound 1%, polyol 2%, and the balance is water.
[0033] Among them, the persulfate is potassium persulfate; the organic acid is malic acid; the sulfonated cyclodextrin is sulfobutyl - β - cyclodextrin; the acidic ionic liquid containing bisulfate is N - ethylpyridinium bisulfate; the fluorine compound is ammonium fluoride; the polyol is glycerol.
[0034] The preparation method is: mix the persulfate, organic acid, sulfonated cyclodextrin, acidic ionic liquid containing bisulfate, fluorine compound, polyol and water evenly according to the above formula to obtain it.
[0035] Example 3 A highly stable and long - life copper - titanium etching solution, by mass percentage, includes the following components: persulfate 15%, organic acid 3%, sulfonated cyclodextrin 0.5%, acidic ionic liquid containing bisulfate 0.1%, fluorine compound 0.05%, polyol 0.01%, and the balance is water.
[0036] Among them, the persulfate is sodium persulfate; the organic acid is tartaric acid; the sulfonated cyclodextrin is sulfobutyl - β - cyclodextrin; the acidic ionic liquid containing bisulfate is 1 - hydroxyethyl - 3 - methylimidazolium bisulfate; the fluorine compound is potassium fluoride; the polyol is mannitol.
[0037] The preparation method is: mix the persulfate, organic acid, sulfonated cyclodextrin, acidic ionic liquid containing bisulfate, fluorine compound, polyol and water evenly according to the above formula to obtain it.
[0038] Comparative Example 1 The preparation method of Comparative Example 1 is the same as that of Example 1, except that an equal mass of sulfosalicylic acid is used to replace sulfonated cyclodextrin.
[0039] Comparative Example 2 The preparation method of Comparative Example 2 is the same as that of Example 1, except that an equal mass of β-cyclodextrin is used to replace sulfonated cyclodextrin.
[0040] Comparative Example 3 The preparation method of Comparative Example 3 is the same as that of Example 1, except that an equal mass of sodium bisulfate is used to replace the acidic ionic liquid containing bisulfate.
[0041] Comparative Example 4 The preparation method of Comparative Example 4 is the same as that of Example 1, except that the acidic ionic liquid containing bisulfate is not added.
[0042] Comparative Example 5 The preparation method of Comparative Example 5 is the same as that of Example 1, except that sulfonated cyclodextrin is not added.
[0043] Performance Test 1. Etching Effect The etching effects of the copper-titanium etching solutions prepared in Examples 1-3 and Comparative Examples 1-5 were tested. At 26 °C, an etching machine was used to etch a copper-titanium substrate (Cu / Ti = 7500 / 100 Å). The total etching time was 2.0 times the EPD. The EPD is the time required for the copper-titanium substrate to just become transparent during the etching process, that is, the etching end point time. By controlling the total etching time to be 2.0 times the EPD, the formation of the etching cone angle can be ensured to meet the target requirements. After the etching was completed, the copper-titanium substrate was taken out, washed and dried, and then a scanning electron microscope (SEM) was used to observe the cone angle, CD bias (critical dimension deviation, characterized by the undercut amount at the bottom of the Cu metal film layer in this test), and tail (tail, measured for titanium tail in this test) to evaluate the etching effect. The results are shown in Table 1 and Figure 1-8 as shown.
[0044] Table 1 Etching Effect of Copper-Titanium Substrate ; Figure 1 - Figure 8 Correspond to the etching effects of the copper-titanium etching solutions prepared in Examples 1-3 and Comparative Examples 1-5 respectively.
[0045] From Table 1 and Figure 1-8It can be seen that the etching effects of Examples 1-3 are better than those of Comparative Examples 1-5. Among them, from Example 1 compared with Comparative Examples 1 and 2, it can be seen that in the etching solution formulation of the present invention, using sulfonated cyclodextrin can better adjust the etching rates of copper and titanium compared with sulfosalicylic acid or β-cyclodextrin, ensuring uniform etching; from Example 1 compared with Comparative Example 3, it can be seen that using an acidic ionic liquid containing bisulfate in the etching solution formulation of the present invention can effectively prevent the occurrence of local over-etching compared with sodium bisulfate, and the imidazole-based cation is selectively adsorbed on the copper-titanium surface, reducing the long trailing phenomenon caused by incomplete etching of titanium. From Example 1 compared with Comparative Examples 4 and 5, it can be seen that in the etching solution formulation of the present invention, using sulfonated cyclodextrin and an acidic ionic liquid containing bisulfate, the two act together to synergistically regulate the uniformity of the etching rate with the main oxidant persulfate, inhibit lateral corrosion, and reduce the trailing phenomenon.
[0046] 2. Stability evaluation Copper powder was added to the etching solutions prepared in Examples 1-3 and Comparative Examples 1-5 for dissolution. After the copper ions in the etching solution reached 8000 ppm, the etching solutions were stored in the dark at room temperature, and the etching capabilities of the etching solutions on the substrate (Cu / Ti = 7500 / 100 Å) were investigated at the initial stage, 4 h, 8 h, 12 h, and 14 h respectively. The CD bias and trailing tail were observed using a scanning electron microscope (SEM) to evaluate the etching effect, and the results were recorded in Table 2 according to the following evaluation criteria: 〇: 0.4 μm < CD bais ≤ 0.6 μm; Δ: 0.6 μm < CD bais < 1.0 μm; ×: CD bais ≤ 0.4 μm or ≥ 1.0 μm; 〇: tail ≤ 0.20 μm; Δ: 0.20 μm < tail < 0.30 μm; ×: tail ≥ 0.30 μm.
[0047] Table 2 Etching effect after dissolving copper powder ; "-" indicates that when the evaluation of CD bais or tail is "×", no subsequent tests are carried out, indicating that the stability of the etching solution does not meet the requirements.
[0048] As can be seen from Table 2, the etching stability of the etching solution provided by the present invention is better. From Example 1 compared with Comparative Examples 1 and 2, it can be seen that sulfonated cyclodextrin helps to improve the stability of the etching solution compared with sulfosalicylic acid and β-cyclodextrin; from Example 1 compared with Comparative Example 3, it can be seen that an acidic ionic liquid containing bisulfate can ensure that the etching solution maintains excellent etching performance for a long time compared with sodium bisulfate; from Example 1 compared with Comparative Examples 4 and 5, it can be seen that in the present invention, sulfonated cyclodextrin and an acidic ionic liquid containing bisulfate act together to effectively inhibit the ineffective decomposition of persulfate ions and significantly enhance the stability of the etching solution.
[0049] 3. Life Evaluation The copper layer of the copper-titanium substrate is relatively thick, and a large amount of copper ions will be generated during the etching process. These accumulated copper ions will react with the key components in the etching solution (such as persulfate as the main oxidant), consuming their effective concentration or reducing their redox potential, thereby weakening the etching ability. In addition, the accumulation of copper ions will also interfere with the functions or synergistic effects of other components, resulting in the deterioration of the etching performance, and ultimately seriously affecting the efficiency and service life of the etching solution. Therefore, taking copper ions as the main influencing factor, the copper dissolution amount is used in this embodiment to characterize the life of the copper etching solution.
[0050] Copper powder was added to the etching solutions prepared in Examples 1-3 and Comparative Examples 1-5 for dissolution. When the copper ion concentration in the etching solution reached 4000 ppm, 6000 ppm, 8000 ppm, 10000 ppm, 12000 ppm, and 14000 ppm, they were respectively poured into the etching machine. At 26 °C, the copper-titanium substrate (Cu / Ti = 7500 / 100 Å) was etched, and the total etching time was 2.0 times the EPD. The EPD is the total time when it is observed that all the copper and titanium are etched during the etching process. By controlling the total etching time to be 2.0 times the EPD, the formation of the etching cone angle can be ensured. The scanning electron microscope (SEM) was used to observe the CD bias and the tail to evaluate the etching effect, and the results were recorded in Table 3 according to the following evaluation criteria: 〇: 0.4 μm < CD bais ≤ 0.6 μm; Δ: 0.6 μm < CD bais < 1.0 μm; ×: CD bais ≤ 0.4 μm or ≥ 1.0 μm; 〇: tail ≤ 0.20 μm; Δ: 0.20 μm < tail < 0.30 μm; ×: tail ≥ 0.30 μm.
[0051] Table 3 Etching Effects after Dissolving Copper Powders with Different Concentrations ; "-" indicates that when the evaluation of CD bais or tail is "×", the subsequent tests will no longer be carried out, indicating that the copper ion content in the etching solution has exceeded its life.
[0052] As can be seen from Table 3, after the copper ion concentration in the etchants provided in Examples 1-3 gradually increased from 4000 ppm to 12000 ppm, the copper-titanium substrates could all be etched, and the range of the CD bais value was more precise and the tailing value was smaller, indicating that the etchant provided by the present invention had more stable etching performance during the entire etching process and would not show large fluctuations due to the increase in the copper ion concentration. The formula of the present invention could extend the service life of the etchant under the accumulation of copper ions; while in Comparative Examples 1-5, the etching process could not proceed due to the gradual increase in the copper ion concentration in the etchant, that is, the service life of the etchants provided in Comparative Examples 1-5 was shorter under the accumulation of copper ions.
[0053] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention should be included within the protection scope of the present invention.
Claims
1. A highly stable and long - life copper - titanium etching solution, characterized in that, By mass percentage, it includes: persulfate 5-15%, organic acid 3-15%, sulfonated cyclodextrin 0.5-3%, acidic ionic liquid containing bisulfate 0.1-4%, fluorine compound 0.05-1%, polyol 0.01-2%, and the balance is water.
2. A highly stable and long-life copper-titanium etching solution according to claim 1, characterized in that, The persulfate is selected from at least one of potassium persulfate, sodium persulfate, and ammonium persulfate.
3. A highly stable and long-life copper-titanium etching solution according to claim 1, characterized in that, The sulfonated cyclodextrin is sulfobutyl-β-cyclodextrin.
4. A highly stable and long - life copper - titanium etching solution as claimed in claim 1, characterized in that, The acidic ionic liquid containing bisulfate is selected from at least one of imidazole bisulfate ionic liquids, pyridine bisulfate ionic liquids, and pyrrolidone bisulfate ionic liquids.
5. The highly stable and long-life copper-titanium etching solution according to claim 4, characterized in that, The imidazole bisulfate ionic liquids are selected from at least one of 1-butyl-3-methylimidazole bisulfate, 1-carboxymethyl-3-methylimidazole bisulfate, and 1-hydroxyethyl-3-methylimidazole bisulfate; The pyridine bisulfate ionic liquids are selected from at least one of N-ethylpyridine bisulfate, N-butylpyridine bisulfate, and N-hexylpyridine bisulfate; The pyrrolidone bisulfate ionic liquids are selected from at least one of 2-pyrrolidone bisulfate, 1-methyl-2-pyrrolidone bisulfate, and 1-(3-sulfonic acid group)-propyl-2-pyrrolidone bisulfate.
6. A highly stable and long - life copper - titanium etching solution according to claim 1, characterized in that, The fluorine compound is selected from at least one of hydrofluoric acid, ammonium fluoride, potassium fluoride, sodium fluoride, ammonium bifluoride, potassium bifluoride, and sodium bifluoride.
7. A highly stable and long-life copper-titanium etching solution as described in claim 1, characterized in that, The organic acid is selected from at least one of citric acid, malic acid, acetic acid, propionic acid, oxalic acid, lactic acid, tartaric acid, and succinic acid.
8. A highly stable and long-life copper-titanium etching solution as described in claim 1, characterized in that, The polyol is selected from at least one of diethylene glycol, ethylene glycol, glycerol, 1,2-propanediol, 1,4-butanediol, pentaerythritol, mannitol, and xylitol.
9. A preparation method of a highly stable and long-life copper-titanium etching solution as described in any one of claims 1-8, characterized in that, According to the required ratio of the copper-titanium etching solution, persulfate, organic acid, sulfonated cyclodextrin, acidic ionic liquid containing bisulfate, fluorine compound, polyol, and water are mixed to obtain it.
10. Application of a copper-titanium etching solution with high stability and long life as described in any one of claims 1-8 in etching copper-titanium laminated materials.
Citation Information
Patent Citations
Copper-titanium etching solution and preparation method thereof
CN120006294A
Etchant composition, and method for manufacturing metal pattern and array substrate using the same
KR1020200068131A